ANALISIS HUTANG DAGANG DAN PENGARUHNYA TERHADAP PENJUALAN (Studi Kasus pada PT. Goodyear Indonesia Tbk. dan PT. Gajah Tunggal Tbk.) - Muhammad Nur Rizqi (Jurnal Ilmiah Binaniaga, 2011)
Accounts payable are the charges arising from the purchase of raw materials, supplies, or merchandise are made on credit to other parties for which payment is deferred until the debt matures. Loose debt policy could result in higher amount of debt a company has, so it can increase the risk of inability to pay , which in turn can lower the profit achievement. For that the company needs to establish appropriate policies to manage its debt. The results of the analysis of trade payables and pengeruhnya on sales at PT. Goodyear Indonesia Tbk. and PT. Gajah Tunggal Tbk. shows that the value of r = 0.630 approaching +1, meaning accounts payable has a strong and positive relationship to sales, this means that an increase in accounts payable each will be followed by an increase in sales. T-test results of the processing of the data above , provide information that amounted to 1,404 t , while t table at the confidence level α ( alpha ) by 10 % or 0.1 and degrees of freedom (df) equal to 3 is 2.353. It can be concluded that t is smaller than t table or 1.404 < 2.353, this means accounts payable does not have a significant impact on sales, in other words, accounts payable does not have a significant effect on sales. Value of r = 0.630 shows values approaching +1, meaning accounts payable has a strong and positive relationship to sales. T-test results of the processing of the data above , provide information that amounted to 1,404 t, while t table at the confidence level α ( alpha ) by 10 % or 0.1 and degrees of freedom (df) equal to 3 is 2.353 . It can be concluded that t is smaller than t table or 1.404 < 2.353, this means accounts payable does not have a significant impact on sales, in other words, accounts payable does not have a significant effect on sales.Keywords : accounts payable, sales.